Soccer injuries in players aged 7 to 12 years: A descriptive epidemiological study over 2 seasons - Rössler, R.; Junge, A.; Chomiak, J.; Dvorak, J.; Faude, O. (The American Journal of Sports Medicine, 2016)
Background: As part of a risk-management approach, sound epidemiological data are needed to develop prevention programs. A recent review on soccer injuries of players younger than 19 years concluded that prospective data concerning children are lacking.